Avaliação da qualidade de forragem hidropônica de centeio, cevada e ervilhaca - Zorzan, Marise Helena Saldanha (2006)
It was carried an experiment, in the Fitotecnia Department of the Federal University of Santa Maria (UFSM) - RS, with objective to evaluate the nutritional quality of two species of grassy (Hordeum vulgare L. and Secale cereale L.), cultivated in hydroponic, during of autumn and winter and to evaluate the nutritional quality of two species of grassy (Hordeum vulgare L. and Secale cereale L) joined to a legume (Vicia sativa L.), cultivated in hydroponic, during autumn and winter. It was adopted the experimental delineation entirely casuistic with four repetitions. The data had been submitted to the variance analysis. The averages of the qualitative variables had been compared among themselves for Tukey test with 5% of error probability. The hydroponic Secale cereale L forage showed bigger dry mass and mineral substance in autumn and winter, surpassing the Hordeum vulgare L forage, Hordeum vulgare L.: intercropping+Vicia sativa L and Secale cereale L+Vicia sativa L. Hydroponic Secale cereale L forage intercropping+Vicia sativa L 150 presented bigger dry mass than the others treatments, however, the mineral substance resulted in minors values, what negatively differentiated in relation the Secale cereale L forage. The biggest fiber value in neutral detergent found, was in the hydroponic Hordeum vulgare L. forage, although it did not show significant difference in relation to the others treatments. The hydroponic Secale cereale L forage presented a bigger rude protein value in relation to the others treatments. The hydroponic forages it did not show significant difference in relation to energetic value and value of phosphorus. The biggest value of calcium and magnesium had been found in the hydroponic Secale cereale L. forage. The Hordeum vulgare L. produced in the 2002 winter, presented minors potassium value, differing significantly from the Hordeum vulgare L intercropping + Vicia sativa L 300 and Secale cereale L + Vicia sativa L 150.